A Semantic Framework for Delivery of Context-Aware Ubiquitous Services in Pervasive Environments - Amato, A.; Di Martino, B.; Venticinque, S. (2012 4th International Conference on Intelligent Networking and Collaborative Systems, 2012)
Pervasive environments offer to software applications the possibility to interact with the reality in order to perceive the information surrounding the users and to adapt the environment itself, or to deliver context aware services that improve user's satisfaction. These services are able to respond in a rational way in many different situations choosing the actions with the best expected result, so making environment not just more connected and efficient, but smarter. In order to provide a pervasive environment with advanced smart capabilities services, we integrated those technologies that enable objects of the real world to become part of the Internet of Things. Besides semantic-based techniques have been used to dynamically and efficiently data processing, retrieval and delivery. Here we present a semantic framework that provides the technology for the development of intelligent, context aware services and their delivery in pervasive environments.